PENGARUH PEMBERDAYAAN DAN LEADER MEMBER EXCHANGE TERHADAP KINERJA KARYAWAN DENGAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI (STUDI PADA RUMAH SAKIT BAITUL HIKMAH KENDAL BAGIAN MEDIS) - Huda, Haris Ihsanil; Rijanti, Tristiana (Jurnal Ilmiah Telaah Manajemen, 2016)
This study was conducted with the aim of analyzing the effect of Empowerment to Self Efficacy, the effect of Leader Member Exchange (LMX) to Self Efficacy, the effect of Empowerment to Performance , the effect of Leader Member Exchange (LMX to Performance, the effect of Self Efficacy to Performance, the role of Self Efficacy as mediation variblethe effect of Empowerment to Performance and the role of Self Efficacy as mediation variblethe effect of LMX to Performance. This research was conducted with a sensus method with 100 respondent.Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. Based on data analysis shows that: 1) Empowerment positive effect on Self Efficacy. (2) Leader Member Exchange (LMX) positive effect on Self Efficacy. (3) Empowerment positive effect on employee performance. (4) Leader Member Exchange (LMX) positive effect on employee performance. and, (5) Self Efficacy positive effect on employee performance. (6) Self Efficacy as mediation variable the effect of empowerment on employee performance. (7) Self Efficacy as mediation variable the effect of the leader member exchange (LMX) on employee performance. Keywords:Empowerment, Leader Member Exchange (LMX), Self Efficacy and Employee Performance.